Implementasi Model Pembelajaran Discovery Learning Pada Mata Pelajaran Instalasi Motor Listrik - Saputra, Rezi; Aswardi, Aswardi (Jurnal Pendidikan Teknik Elektro, 2024)
This study was conducted to know the impact of implementing the discovery learning model on the learning outcomes of electric motor installation of students in class XI TITl SMK Dhuafa Padang. This research uses quantitative methods in the from of a pre-experimental design with a one-group pretest-posttest design. The participants of this study were XI grade TITL students at SMK Dhuafa Padang. This study used instruments in the form of multiple-choice written test questions arranged based on the material and learning objectives to be achieved based on the curriculum. In this study, an instrument test was conducted to determine the validity, reliability, level of difficulty of the questions, and the differentiation of the questions. The data analysis technique used is classical completeness of students' learning outcomes, t-test, and effect size analysis. Based on the result of the research and discussion that has been carried out, it shows that the average value of students' posttest learning outcomes has increased which can be seen in many students who get scores that reach the criteria for achievement of learning objectives effect size analysis is in the large category. Therefore, the researcher concluded that implementation of the discovery learning model in the subject of electric motor installation at SMK Dhuafa Padang has an impact on improving students' learning outcomes.